Beyond the Medical Model: Future Directions for Suicide Intervention Services. (January 2018) - Fitzpatrick, Scott J.; River, Jo
The medical model continues to dominate research and shape policy and service responses to suicide. In this work we challenge the assumption that the medical model always provides the most effective and appropriate care for persons who are suicidal. In particular, we point to service user perspectives of health services which show that interventions are often experienced as discriminatory, culturally inappropriate, and incongruent with the needs and values of persons who are suicidal. We then examine "humanistic" approaches to care that have been proposed as a corrective to an overly medical model. We argue that the focus on improving interpersonal relations set out in humanistic approaches does not mitigate the prevailing risk management culture in contemporary suicide prevention and may impede the provision of more effective care. Finally, we draw attention to the tradition of non-medical approaches to supporting persons who are suicidal. Using Maytree (a U.K. crisis support service) as a case study, we outline some of the key features of alternative service models that we consider central to the design of more culturally appropriate and effective interventions. We conclude by making three key recommendations for improving services to persons who are suicidal.